SPECIAL ASPECTS OF USING A MENTORING APPROACH TO TRAINING PUBLIC RELATIONS SPECIALISTS - Andrii Kyrychok (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
This article presents the peculiarities of using mentoring approach to training public relations (PR) specialists. It includes a historiographical overview of the best practices related to the specifics of using mentoring in education. Based on the literature review, it proves that the use of a mentoring approach to training PR specialists has certain peculiarities and advantages. This paper provides the results of the study in the form of an online survey. Participants were practitioners and teachers working in the PR field. They had to answer questions related to the methodology of PR professional training at universities. Based on the data obtained, the main issues of mentoring assistance in preparing PR specialists have been discussed. The key methodological aspect of using mentoring assistance in PR training is using a pedagogical model "show-tell-do". This article covers general recommendations on integrating the mentoring approach into the process of PR specialist training at the university.